Entwicklung von Stadt und Verkehr in deutschen Großstädten / Shanghai. Ergebnisse vergleichender Untersuchungen. - Zhang, Ying (Deutscher Verkehrs-Verl., 2004)
Die chinesische Metropole Shanghai, befindet sich seit über zwei Jahrzehnten in einem tiefgreifenden Wandel von Wirtschaft, Stadtentwicklung und Verkehr. Die Verkehrsinfrastruktur wurde durch beträchtliche Neu- und Ausbauten verbessert. Trotzdem nehmen die Verkehrsprobleme ständig zu. Staus und Behinderungen des Straßenverkehrs sind an der Tagesordnung. Besonders betroffen ist die Innenstadt. difu

As holder of a DMD scholarship, the author has spent the last four years at the Technical University of Munich (Chair for Transport and Urban Planning held by Prof. Dr.-Ing. Peter Kirchhoff). The research carried out has focused on the urban development of, and transport in, Munich (her residence), Hamburg (largest seaport in Germany), Dresden (example of a major German city of the former GDR), and Shanghai by form of comparison. Her research into, and comparison of, urban expansion and traffic growth has shown that the results have tended to be basically the same for all these cities. In the case of Shanghai, however, the quantitative and qualitative level of development has been lower while its dynamism has been a prominent feature over the last few years. The knowledge gained, and findings gathered her research into cases related to Germany - together with any general and specific recommendations - should be passed on to the concerned authorities in Shanghai for further review. difu
Keywords: Stadtverkehr; Verkehr; ÖPNV; Individualverkehr; Verkehrsinfrastruktur; Verkehrssystem; Stadtplanung; Stadtentwicklung; Verkehrsmittelwahl; Vergleichsuntersuchung; Städtevergleich; Ballungsraum; Verkehrsmittelnutzung